2013
DOI: 10.1039/c3ta13291a
|View full text |Cite
|
Sign up to set email alerts
|

Tubular graphitic-C3N4: a prospective material for energy storage and green photocatalysis

Abstract: We have established a facile and scaleable approach to fabricate tubular graphitic-C3N4 using melamine. The construction of the unique tubular morphology is a result of the pre-treatment of melamine with HNO3. Herein, for the first time, we have explored the electrochemical properties of g-C3N4 as an electrode material for supercapacitors. Tubular g-C3N4 has significant advantages due to its distinctive morphology, high surface area (182.61 m 2 g -1 ) and combination of carbon with nitrogen. Therefore, tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(121 citation statements)
references
References 46 publications
3
115
1
2
Order By: Relevance
“…For BiOCl and Bi 2 S 3 , the values of n are 4 and 1, respectively [41]. Thus, the E g estimated from the intercept of the tangents to the plot of (αhυ) 1/2 versus hυ was 3.20 eV for BiOCl while the E g from the plot of (αhυ) 2 versus hυ was 1.46 eV for Bi 2 S 3 and 1.68, 2.0, 2.31, 2.81, 3.05 for C1, C2, C3, C4, C5 hetero-structure composites, respectively (Figs. S4, S5).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For BiOCl and Bi 2 S 3 , the values of n are 4 and 1, respectively [41]. Thus, the E g estimated from the intercept of the tangents to the plot of (αhυ) 1/2 versus hυ was 3.20 eV for BiOCl while the E g from the plot of (αhυ) 2 versus hυ was 1.46 eV for Bi 2 S 3 and 1.68, 2.0, 2.31, 2.81, 3.05 for C1, C2, C3, C4, C5 hetero-structure composites, respectively (Figs. S4, S5).…”
Section: Resultsmentioning
confidence: 96%
“…The shape-and structure-dependent effects could develop, widespread and versatile potential applications. So, the morphological and structural tailoring of nano-/micro-crystals has emerged as an challenge [1][2][3]. Recently, hollow nanostructures, core-shell nanostructures and hetero-structures as a kind of new nano-/micro-structures have received an intense attention because of their improved physical and chemical properties over their single components [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Tahir et al 49 synthesized the tubular g-C 3 N 4 and investigated the electrochemical properties which suggest it to be a good contestant for a supercapacitor and photocatalyst used for cleaning environment and energy storage purpose. Recently Wang et al 50 synthesized the nanotube g-C 3 N 4 material and demonstrated the intense uorescence with a photoluminescent, reecting the applications as a blue light uorescence material.…”
Section: -47mentioning
confidence: 99%
“…Tanveer, M., Cao, C., Ali, Z., Aslam, I., Idrees, F., Khan, W. S., But, F. K., Tahir, M. & Mahmood, N. (2014 Well controlled nanosheets-based hierarchical microspheres (NSHMS) of pure covellite phase CuS were synthesized using a facile PVP assisted solvothermal process. The reaction conditions were optimized using various amounts of PVP to develop unique hierarchical structured hollow microspheres.…”
Section: Publication Detailsmentioning
confidence: 99%